Jesus wept: the Roman Catholic Church, child sexual abuse and transitional justice - Gallen, James (International journal of transitional justice, 2016)
This article considers the range of issues involved in pursuing justice for the sexual and institutional abuse of children by the Roman Catholic Church. It examines whether the framework of transitional justice discourse and practice should be used to analyze how individuals, communities, states and the global Roman Catholic Church can and should respond to the church’s legacy of widespread child sexual abuse committed by priests and religious individuals. It interrogates whether transitional justice should be employed in a novel non-armed conflict setting and argues that measures taken to date fail to reflect key insights of transitional justice that could be usefully applied to the church’s response to this pattern of abuse.